Role of nanorods insertion layer in ZnO-based electrochemical metallization memory cell. (9th November 2017) - Simanjuntak, Firman Mangasa; Singh, Pragya; Chandrasekaran, Sridhar; Lumbantoruan, Franky Juanda; Yang, Chih-Chieh; Huang, Chu-Jie; Lin, Chun-Chieh; Tseng, Tseung-Yuen
Abstract: An engineering nanorod array in a ZnO-based electrochemical metallization device for nonvolatile memory applications was investigated. A hydrothermally synthesized nanorod layer was inserted into a Cu/ZnO/ITO device structure. Another device was fabricated without nanorods for comparison, and this device demonstrated a diode-like behavior with no switching behavior at a low current compliance (CC). The switching became clear only when the CC was increased to 75 mA. The insertion of a nanorods layer induced switching characteristics at a low operation current and improve the endurance and retention performances. The morphology of the nanorods may control the switching characteristics. A forming-free electrochemical metallization memory device having long switching cycles (>10 4 cycles) with a sufficient memory window (10 3 times) for data storage application, good switching stability and sufficient retention was successfully fabricated by adjusting the morphology and defect concentration of the inserted nanorod layer. The nanorod layer not only contributed to inducing resistive switching characteristics but also acted as both a switching layer and a cation diffusion control layer.